2021
DOI: 10.3390/cancers13215526
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Differentiates Lymphoma Patients with and without Concurrent Myeloproliferative Neoplasia

Abstract: Myeloproliferative neoplasia (MPN) and lymphoma are regarded as distinct diseases with different pathogeneses. However, patients that are diagnosed with both malignancies occur more frequently in the population than expected. This has led to the hypothesis that the two malignancies may, in some cases, be pathogenetically related. Using a mass spectrometry-based proteomic approach, we show that pre-treatment lymphoma samples from patients with both MPN and lymphoma, either angioimmunoblastic T-cell lymphoma (MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Over the past decade, researchers using proteomic approaches have provided information on quantitative and qualitative protein patterns in the blood to identify potential cancer biomarkers. 8,9 However, only a minority of published lymphoma proteomic studies have investigated protein expression in patient blood samples, [10][11][12][13][14][15] particularly samples from patients with AIDS-NHL. Xu et al 16 used surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS) to build four models of serum protein fingerprints for identifying potential biomarkers of diffuse large B-cell lymphoma (DLBCL) and distinguishing prognostic markers.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, researchers using proteomic approaches have provided information on quantitative and qualitative protein patterns in the blood to identify potential cancer biomarkers. 8,9 However, only a minority of published lymphoma proteomic studies have investigated protein expression in patient blood samples, [10][11][12][13][14][15] particularly samples from patients with AIDS-NHL. Xu et al 16 used surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS) to build four models of serum protein fingerprints for identifying potential biomarkers of diffuse large B-cell lymphoma (DLBCL) and distinguishing prognostic markers.…”
Section: Introductionmentioning
confidence: 99%
“…Splenic infiltration is often seen in DLBCL, but type of primary splenic DLBCL is rare and studies on its clinicopathological features are limited. Holst J. et al evaluate patients with confirmed dual diagnoses of myeloproliferative neoplasm and lymphoma [15]. They found that the 5-year overall survival rate of the patients with MPN+DLBCL was 19% as compared to 34% for patients in the matched reference cohort with presence only DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…To identify differentially expressed proteins between the samples, a label-free quantification nano liquid chromatography-tandem MS–based proteomic analysis was performed. 26 , 27 The procedure is described in detail in the supplemental Methods . In brief, proteins from formalin-fixed, paraffin-embedded lymphoma tissues were extracted and proteolytically digested into peptides.…”
Section: Methodsmentioning
confidence: 99%